Aplicação do modelo Pressão-Estado-Resposta (PER) em área susceptível à contaminação com resíduos de óleos lubrificantes - Santos, Fabiana Silva (2013)
Concern about environmental impacts involving petroleum, lubricants such, it is a fact today. The automotive lubricants suffer deterioration due to its use, which modifies its composition and properties, becoming known: used or contaminated lubricating oil - OLUC. The oily residue is considered a dangerous contaminant of natural ecosystems when disposed of improperly. This study conducted in the District Mechanic City João Pessoa / PB, a study on the management OLUC, from generation to final disposal, as well as evaluating the environmental aspects of the area face the disposal of these wastes. The collected data were classified based on the conceptualized model PER - pressure-state-response. It was concluded that the formal procedures of collecting OLUC are not being performed as established by CONAMA Resolution nº. 362/2005, establishments lack of preventive spill OLUC, among others. The construction of a frame based on the PER model can be considered a starting point for development of projects aimed at local improvements, help clarify and identify the causes of environmental problems with OLUC and contribute to sustainability of the local area and remote areas that are under the influence of anthropogenic activities practiced in the District Mechanic.